Adverse transition of smoking stages among lower secondary school students of Kinta, Perak: A prospective cohort study / Premila Devi Jeganathan - Premila Devi , Jeganathan (2016)
Smoking behaviour normally begins with initiation during adolescence and progress through different stages. Yet, few prospective longitudinal researches have been conducted to examine the influence of various factors on progression to a higher smoking stage. The aim of this study was to describe the factors associated with adverse transition of smoking stages among adolescents. A school-based study among a cohort of 2552 secondary students aged 12 to 13 years old was conducted. Data collection was conducted twice, 12 months apart. Students answered a self-administered questionnaire. In this study, adverse transition was defined as transition from one smoking stage to a more adverse stage during follow up. The procedures in the complex samples add-on module were used in the analyses after adding appropriate student and school weights that were adjusted for non-response. The predictors of the four adverse transitions were tested using multinomial logistic regression analysis. The results at Time 1 indicated that there were never smokers, 474 susceptible never smokers, 168 experimenters and 83 ex-smoker in this study. At Time 2, 77.2% of the never smokers remained stable never, while 22.8% had Adverse Transition I. Adverse Transition II was 27.8 % among the susceptible never smokers. Among the experimenters, 43.5% had adverse Transition III and 36.0% of the ex-smokers had adverse Transition IV. The analysis of this study demonstrates that adverse transition of smoking stages was associated with various socio-demographic, school, peer, parental and personal factors. Among these variables, five factors were associated with all four adverse transitions groups.This study demonstrates the presence of different groups of adverse transition among adolescents and the various factors that can influence these transitions. Ethnicity, school adjustment, having a best friend who smokes, self-efficacy and perceived ease of accessibility to purchase cigarettes were associated with all four adverse transitions groups. Development of interventions against adverse transition among adolescents should be iv multi-faceted and consideration should be given to using different strategies based on the various influencing factors to target the different smoking stages.